2009
DOI: 10.1534/genetics.109.101329
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Analysis of Zinc-Finger Nuclease-Induced Gene Targeting in Drosophila

Abstract: Using zinc-finger nucleases (ZFNs) to cleave the chromosomal target, we have achieved high frequencies of gene targeting in the Drosophila germline. Both local mutagenesis through nonhomologous end joining (NHEJ) and gene replacement via homologous recombination (HR) are stimulated by target cleavage. In this study we investigated the mechanisms that underlie these processes, using materials for the rosy (ry) locus. The frequency of HR dropped significantly in flies homozygous for mutations in spnA (Rad51) or … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
92
0
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 105 publications
(96 citation statements)
references
References 55 publications
(82 reference statements)
3
92
0
1
Order By: Relevance
“…By contrast, the alternative pathway of homology-directed repair (HDR) can be utilized for the introduction of precise genetic modifications such as codon replacements or reporter insertions by recombination with exogenous targeting vectors, serving as repair template 5 . We reasoned that the efficiency of HDR and thus the construction of precise genetic modifications could be boosted by the transient inhibition of NHEJ key molecules, similar to what has been observed for Drosophila embryos with a genetic DNA Ligase IV deficiency 6 .…”
mentioning
confidence: 82%
“…By contrast, the alternative pathway of homology-directed repair (HDR) can be utilized for the introduction of precise genetic modifications such as codon replacements or reporter insertions by recombination with exogenous targeting vectors, serving as repair template 5 . We reasoned that the efficiency of HDR and thus the construction of precise genetic modifications could be boosted by the transient inhibition of NHEJ key molecules, similar to what has been observed for Drosophila embryos with a genetic DNA Ligase IV deficiency 6 .…”
mentioning
confidence: 82%
“…Knocking out NHEJ had no effect on crossover frequency ( Figure 1C), despite previous studies in Drosophila that have revealed roles for both NHEJ and HR in repairing DSBs in the male germline (Preston et al 2006;Bozas et al 2009;Beumer et al 2013). These experiments involved enzymatic induction of DSBs, probably throughout the cell cycle.…”
Section: Functions Of Blm In Preventing Mitotic Crossoversmentioning
confidence: 76%
“…We did not observe any decrease in the number of progeny produced by Blm males when they were treated with HU (data not shown), suggesting that cell death was not pervasive, but modest elevations in cell death frequency might still go undetected due to rapid proliferation in the germline. Knocking out NHEJ had no effect on crossover frequency ( Figure 1C), despite previous studies in Drosophila that have revealed roles for both NHEJ and HR in repairing DSBs in the male germline (Preston et al 2006;Bozas et al 2009;Beumer et al 2013). These experiments involved enzymatic induction of DSBs, probably throughout the cell cycle.…”
mentioning
confidence: 76%
“…Whereas this effect could be further enhanced by siRNA-mediated knockdown of the second Ku70 allele (Fattah et al, 2008), knockdown of DNAPKcs did not have an effect on AAV-mediated gene targeting (Vasileva et al, 2006). On the other hand, although it has been shown that Rad51 and Rad54 are essential for both ZFN and AAV-mediated gene targeting (Vasileva et al, 2006;Bozas et al, 2009), human cells stably over-expressing RAD51 revealed only a two-fold increase in conventional, plasmid-based gene targeting (Yanez and Porter, 1999). On the whole, it remains open to discussion whether a genetic intervention to shift the balance in AAV or ZFN-mediated gene targeting from NHEJ to HR is meaningful in a therapeutic context.…”
Section: Discussionmentioning
confidence: 90%